Road lighting automation scenarios depending on traffic speed and volume. (October 2019) - Buyukkinaci, B; Onaygil, S; Guler, O; Yurtseven, MB
In this study, experimental studies that the authors have previously performed on a test road for fixed observer conditions to determine the visibility levels are extended to the moving observer position. As a result of the measurements and tests, when the vehicle speed is constant at the current speed limits for urban roads, it has been seen that the visibility level values in the calculation area remain within the acceptable limits and changing the luminous fluxes will not significantly change the visual performance of the drivers up to two lower lighting classes. It has been shown that the light level can be reduced to create two additional classes besides the current one when the traffic density decreases, at the times when vehicle speeds do not decrease. The results are applied as a case study on the Cendere Street. Road lighting classes are determined according to the EN 13201-1 Technical Report. Road lighting classes that can be applied at different times in the Cendere Street change between M3 and M5 according to the average speed of the passing vehicles, traffic density, road and ambient conditions. It is estimated that about 40% energy saving can be achieved when a lighting automation system is installed.